2011
DOI: 10.1590/s1516-35982011000100024
|View full text |Cite
|
Sign up to set email alerts
|

Sugar cane dry yeast in feeding for growing and finishing goat kids

Abstract: -It was used 27 goat kids (18 ¾ Boer + ¼ Saanen and nine Saanen; 18.0 ± 1.60 kg) distributed in a completely randomized design with factorial arrangement to evaluate productive performance and the total digestibility of dry matter and nutrients in the rations. Diets were composed of soybean meal, soybean meal + dry yeast or dry yeast as protein source, oat hay, ground corn and vitamin-mineral mixture with mean composition of 2.50 Mcal of ME/kg DM and 17.0% of crude protein on average. Digestibility was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
1
6
1
1
Order By: Relevance
“…The observed averages for dry matter intake on prepartum period were 1513.7; 1483.2 and 1538.4 g/day and in the postpartum the averages were 1764.4; 1632.5 and 1660.3 g/day, for diets soybean meal; soybean meal plus dry yeast and dry yeast, respectively, and this suggests that dry yeast and soybean meal have similar acceptability in peripartum goats. Similarly, other studies have shown no effects of dry yeast on dry matter intake in sheep (AGUIAR et al, 2007) and goats (FREITAS et al, 2011;LIMA et al, 2011).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The observed averages for dry matter intake on prepartum period were 1513.7; 1483.2 and 1538.4 g/day and in the postpartum the averages were 1764.4; 1632.5 and 1660.3 g/day, for diets soybean meal; soybean meal plus dry yeast and dry yeast, respectively, and this suggests that dry yeast and soybean meal have similar acceptability in peripartum goats. Similarly, other studies have shown no effects of dry yeast on dry matter intake in sheep (AGUIAR et al, 2007) and goats (FREITAS et al, 2011;LIMA et al, 2011).…”
Section: Resultsmentioning
confidence: 69%
“…However, the digestibility of dry matter and nutrients can be improved when dry yeast is included in diets for heifers and goat kids, as reported by Martins et al (2000) and Lima et al (2011), respectively. Digestibility is directly influenced by the feed intake, diet composition, degradability, protein to energy ratio and factors related to the animals ( VAN SOEST, 1994).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Alcalde et al (2011), working with ¾ Boer + ¼ Saanen kids fed diets containing on average 2.65 Mcal/Kg DM and 3.6% EE formulated with oil seeds, related a food conversion of 6.58. Lima et al (2011) stated that the feed conversion can vary within the same genetic group, depending on the age of the animals and the diets supplied.…”
Section: Resultsmentioning
confidence: 99%
“…Altos níveis de inclusão de levedura seca de cana-de-açúcar na dieta de monogástricos pode prejudicar o desempenho dos animais, pois a baixa digestibilidade da parede celular da levedura reduz a utilização dos nutrientes da ração (Sucupira et al, 2007). O mesmo parece não ocorrer com cabras em lactação (Lima, 2010), cabras em crescimento (Lima et al, 2011) e novilhas em crescimento (Franco et al, 2010), provavelmente em razão de os animais ruminantes apresentarem flora microbiana ruminal que auxilia no processo de digestão da parece celular da levedura, e torna a levedura totalmente degradada no rúmen. Entretanto, essa característica da levedura seca pode aumentar as perdas de nitrogênio na urina e no leite e causar redução na eficiência de utilização do nitrogênio ingerido para a produção ao substituir o farelo de soja.…”
Section: Introductionunclassified